An examination of the relationship between exchange rate and export demand in China / Noorazlina Ahmad, Fadli Fizari Abu Hassan Asari and Sakinah Mat Zin - Ahmad, Noorazlina; Abu Hassan Asari, Fadli Fizari; Mat Zin, Sakinah (2012)
The effect of export performance on exchange rate reflects the increasing degree of financial market integration. They are important for both theoretical and empirical considerations. This study empirically investigates the relationship between export and exchange rate with respect to China. Objectives of this research are to identify whether exchange rate has a significant and direct impact on export volume and also to determine whether there is a long-run equilibrium relationship between the variables in the export demand functions. Specifically, this paper attempts to analyze the impact of exchange rate volatility on export performance. In order to achieve this objective, the Vector Error Correction Model (VECM) is employed to determine whether stock prices affect the exchange rate. Based on 48 years (1962 - 2010) annual data for China, the findings reveal that exchange rate volatility is not effective in the short run.